Evaluation of Local Chicken Slaughter Operation, Carcas and Product Characteristics in Yogyakarta - Wahyu Supartono; Sri Raharjo; Sofyan Iskandar (Indonesian Food and Nutrition Progress, 2002)
Indonesian local chicken has some advantages in compared with broiler chicken. Local chicken can live freely and sometimes serves as "saving" for family in villages. The local chicken is used as raw material for some traditional. This research focused on chemical and microbiological properties on local chicken carcasses and also their finished products, such as satay or fried chicken. Results of this research showed, that local chicken carcasses has more protein content than broiler carcasses, and has also lower calorie and fat content. But their fat and calorie became higher, after their fresh local chicken carcasses were prepared, spiced and fried or grilled ready-to-eat foods. All of fresh local chicken carcasses, which were taken and collected from local slaughtering houses, were contaminated by pathogenic microbes, such as Escherichia coli, Salmonella sp and Staphylococcus sp. But after processing of the fresh carcasses, the number of the pathogenic microbes decreased drastically, so food poisoning or out break of consumers was rarely occurred. The result's of evaluation on gender and socio-economic factors suggested, that local slaughtering house operations were feasible with no possibility to expand their activities. More investment to buy an electrical machine (Feather-Pluckier) was very useful for raising their productivity, capacity and ease in preparing carcasses. The women workers had three job description (owner, main worker and an assistant) in this slaughtering process, and they did not have difficulties to do their job and their loan actually was used to help their own economic family